Comparison of Low-Level Laser versus Intra-Articular Corticosteroid Therapy for Temporomandibular Joint Osteoarthritis in Rats - AbuBakr, Nermeen; Salem, Zeinab Amin; Ali, Zoba Hassan; El Assaly, Manal Safwat (UI Scholars Hub, 2018)
Osteoarthritis (OA) is an increasingly common deteriorating disorder of the temporomandibular joint (TMJ) for which there is an urgent need to improve the prevention and cure. Objectives: We aimed to compare low-level laser (LLL) against corticosteroids as an alternative treatment for TMJ-OA. Methods: Sixty rats with TMJ-OA were divided into OA (untreated), corticosteroid-treated, and LLL-treated groups. Animals were sacrificed at 1 and 4 weeks after treatment, and their TMJs were dissected for evaluation by histological analysis, histochemical analysis, and quantitative real-time polymerase chain reaction. Statistical comparison was conducted using one-way analysis of variance. Results: Histopathological examination revealed degenerative changes and loss of normal architecture in the untreated OA group and that these changes were decreased in both treatment groups. In histochemical analysis, collagen formation was higher in both treated groups than in the untreated group. Finally, tumor necrosis factor-α level was the highest in the OA group, followed by the corticosteroid- and LLL-treated groups. Conclusion: LLL may improve joint OA in the TMJ to a similar extent to corticosteroids and appears to have superior anti-inflammatory effects in the short-term.